2019
DOI: 10.1001/jama.2019.5586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sunscreen Application Under Maximal Use Conditions on Plasma Concentration of Sunscreen Active Ingredients

Abstract: IMPORTANCEThe US Food and Drug Administration (FDA) has provided guidance that sunscreen active ingredients with systemic absorption greater than 0.5 ng/mL or with safety concerns should undergo nonclinical toxicology assessment including systemic carcinogenicity and additional developmental and reproductive studies. OBJECTIVE To determine whether the active ingredients (avobenzone, oxybenzone, octocrylene, and ecamsule) of 4 commercially available sunscreens are absorbed into systemic circulation. DESIGN, SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(216 citation statements)
references
References 11 publications
3
197
0
7
Order By: Relevance
“…Specifically, after 75% body surface application at maximal usage conditions, organic filters were absorbed and had detectable plasma levels. 37 However, the clinical relevance of these findings is completely unknown. Further studies are needed to understand the impact of this information on the safety of organic filters.…”
Section: Safetymyths and Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, after 75% body surface application at maximal usage conditions, organic filters were absorbed and had detectable plasma levels. 37 However, the clinical relevance of these findings is completely unknown. Further studies are needed to understand the impact of this information on the safety of organic filters.…”
Section: Safetymyths and Realitymentioning
confidence: 99%
“…Of note, a recently published study has reported the penetration of topically applied organic filters into the blood circulation of human subjects. Specifically, after 75% body surface application at maximal usage conditions, organic filters were absorbed and had detectable plasma levels . However, the clinical relevance of these findings is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent increased scrutiny from the FDA into all presently available chemical sunscreen filters used in the United States and the recent JAMA article on sunscreen absorption, it is imperative that dermatologists understand what chemical filters are associated with allergy, understand that absorption in compromised skin may be elevated and finally, understand that sunscreen labeling may not help consumers. No sunscreen with allergenic and irritating UV filters, fragrances, preservatives, emulsifiers, etc should hold the labels “sensitive skin” or “hypoallergenic.” It is my opinion that chemical filters should not be used in sunscreens labeled “baby.” It would prove helpful to both consumers and physicians if the FDA mandated strict guidelines for placeholder terms like “sensitive skin,” “hypoallergenic,” and “for kids” not only for sunscreens but for all skincare—in particular those marketed for babies and children.…”
Section: A Widespread Issuementioning
confidence: 99%
“…It is beyond the scope of this editorial and the science is still evolving; however, I think it is important as dermatologists that we continue to review the current literature on this topic. 21 With the recent increased scrutiny from the FDA into all presently available chemical sunscreen filters used in the United States and the recent JAMA article on sunscreen absorption, 22 it is imperative that dermatologists understand what chemical filters are associated with allergy, understand that absorption in compromised skin may be elevated and finally, understand that sunscreen labeling may not help consumers. No sunscreen with allergenic and irritating UV filters, fragrances, preservatives, emulsifiers, etc should hold the labels "sensitive skin" or "hypoallergenic."…”
Section: A Wide S Pre Ad Issuementioning
confidence: 99%
“…However, would such an effect of UVR then work to protect against both the transient and persistent AD subtypes? And should sunscreen be advocated despite systemic absorption that might take place that exceeds regulatory limits following universal application?…”
mentioning
confidence: 99%